2012
DOI: 10.3748/wjg.v18.i40.5669
|View full text |Cite
|
Sign up to set email alerts
|

Levofloxacin/amoxicillin-based schemesvsquadruple therapy forHelicobacter pylorieradication in second-line

Abstract: Worldwide prevalence of Helicobacter pylori (H. pylori) infection is approximately 50%, with the highest being in developing countries. We compared cure rates and tolerability (SE) of second-line anti-H. pylori levofloxacin/amoxicillin (LA)-based triple regimens vs standard quadruple therapy (QT). An English language literature search was performed up to October 2010. A meta-analysis was performed including randomized clinical trials comparing 7- or 10-d LA with 7-d QT. In total, 10 articles and four abstracts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 72 publications
0
26
1
Order By: Relevance
“…Previously it has been reported that the eradication rate of 10-day PAL regimen was higher than that of 7-day PAL regimen 30. However, current study did not show any difference in eradication rates according to treatment duration.…”
Section: Discussioncontrasting
confidence: 82%
“…Previously it has been reported that the eradication rate of 10-day PAL regimen was higher than that of 7-day PAL regimen 30. However, current study did not show any difference in eradication rates according to treatment duration.…”
Section: Discussioncontrasting
confidence: 82%
“…All the included studies were published between 2002 and 2015 in English, with the exception of three studies, which were published in Chinese [ 24 – 26 ]. Six studies exclusively evaluated second-line treatment for patients with at least one prior course of treatment failure [ 27 32 ]; 12 studies focused on treatment naive patients [ 25 , 26 , 33 42 ]; the remaining systematic reviews included RCTs for both first-line and second-line treatment. 13 studies evaluated treatments in patients with comorbid gastric diseases including peptic ulcer disease, duodenal ulcer, functional dyspepsia, chronic gastritis or other non-ulcer diseases [ 24 , 27 , 37 40 , 43 49 ] (the remaining studies did not provide such data).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies compared the effectiveness, adverse events rate and therapy discontinuation rates between triple therapy and bismuth-based therapy [ 27 32 , 38 , 39 , 50 ]. The study characteristics are presented in Table 4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is hardly surprising, as diarrhea and nausea are expected adverse effects for levofloxacin 31 , as well as for amoxicillin 32 , but they did not cause severe discomfort to patients. However, Di Caro et al, when comparing the adverse effects of similar treatments with quadruple therapy, reported a much lower prevalence 33 of adverse effects.…”
Section: Discussionmentioning
confidence: 99%